Generic separating sets for three-dimensional elasticity tensors. (26th June 2019) - Desmorat, R.; Auffray, N.; Desmorat, B.; Kolev, B.; Olive, M.
Abstract : We define a generic separating set of invariant functions (a.k.a. a weak functional basis ) for tensors. We then produce two generic separating sets of polynomial invariants for three-dimensional elasticity tensors, one consisting of 19 polynomials and one consisting of 21 polynomials (but easier to compute), and a generic separating set of 18 rational invariants. As a by-product, a new integrity basis for the fourth-order harmonic tensor is provided.